Epidemiology and associated factors of irritable bowel syndrome in an Andean community from Peru - Alvizuri Gómez, Claudia Mariella; Bellido Caparó, Álvaro; Samalvides Cuba, Frine; Pinto Valdivia, José Luis (Revista de Gastroenterología del Perú, 2021)
Introduction: Irritable bowel syndrome (IBS) is a chronic functional bowel condition with an average world prevalence of 11.2%. Is associated with multiple factors as female sex, young age, stress, anxiety and depression which can have a negative impact on quality of life. IBS in Peru is not investigated at all specially in the Andean region. The objective of this study is to determine the prevalence and associated factors of IBS in an Andean community from Peru using the Rome IV criteria. Materials and methods: Cross-sectional study in a rural community dedicated to livestock and agriculture in Peru at 3,235 meters above sea level. Questionnaires provided by the Rome Foundation as the Rome IV – Diagnostic questionnaire for adults, Irritable Bowel Syndrome - Symptom Severity Scale and Bristol stool scale were used. Results: 130 residents met the inclusion criteria. 46.9% were males with an average age of 54 years old. 11.54% presented red flags and were not included in the analysis. 13.1% were diagnosed with IBS and 52.9% presented constipation as predominant bowel pattern. 52.9% presented a mild course of the disease. In the chi-square analysis, factors as depression, anxiety, female sex, younger age, liquefied petroleum gas exposure for cooking and education achievement were statistically significant associated to IBS. In the logistic regression analysis, anxiety was the unique independent predictor factor with an OR of 9.6 (95% IC: 1.78-51.82). Conclusion: IBS is a prevalent condition in the Andean region and should be managed as a public health issue to improve quality of life.